COVID-19 Pandemic: The Urgent Dental Hub experience from a primary care perspective. Issue 3 (September 2021) - Khwaja, Zohaib; Ali, Awais; Rai, Manraj
In response to the nationwide lockdown on 23 March 2020 in the UK, urgent dental hubs (UDHs) were established in the community to provide emergency dental care. Consecutive referrals to a primary care UDH were prospectively analysed over a one-month period, from 18 May 2020 to 18 June 2020. Of 400 referrals received, the most common were in relation to pain (87%). In 63% neither a radiograph nor photograph was provided with the referral. Seventy percent of patients were telephone triaged within 24 hours of receipt of referral. Fifty-three percent of referrals were accepted for face-to-face treatment, of which 69% were treated by extraction. Of rejected referrals (n=179; 45%), 79% were due to symptoms having settled or being manageable by the time of triage. A small number of referrals were redirected for specialist care. Referrals that were accepted were more likely to have been prescribed antibiotics and less likely to have been referred by the general dental practitioner (GDP) they regularly saw (p <0.01). Patients that were older and those that identified themselves as not having a regular GDP were less likely to have been referred to an UDH. The quality of referrals was poor and there may be a role for virtual consultations moving forwards. We found pre-referral antimicrobial prescriptions were high and a confused public health message may have been sent.